Non-destructive imaging of marqueteries based on a new infrared-terahertz fusion technique - Hu, Jue; Zhang, Hai; Sfarra, Stefano; Gargiulo, Gianfranco; Avdelidis, Nicolas P.; Zhang, Mingli; Yang, Dazhi; Maldague, Xavier P. (Elsevier, 2022)
Detection of subsurface defects has hitherto been regarded as an important element in the course of preserving cultural heritage. To do so, non-destructive imaging approaches for viewing and determining the location of splitting inside the sample under test are required, which constitute the subject of the present study. Both active thermography and terahertz imaging have demonstrated their potential in providing non-destructive inspection on cultural heritage objects. Conventionally, active thermography has been used to retrieve details on the defects as well as morphological data from the surface and subsurface, whereas pulsed terahertz imaging has been applied to record the internal material distribution. Here, the feature extraction, selection and fusion framework is extended to design a fusion process to merge the information obtained by both active thermography and terahertz imaging; in this way, the technique naturally inherits the strengths of both aforementioned imaging technologies. The fusion technique is able to produce images with high-contrast defect information located at different depths. To demonstrate the efficacy of the suggested technique, an experiment has been conducted on an ancient marquetry.
Keywords: Cultural heritage; Infrared thermography; Terahertz imaging; Data fusion